PROBLEMS OF LEGAL REGULATION OF AIR TRANSPORTATIONS OF PASSENGERS AND LUGGAGE IN UKRAINE - Білоусов, В. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article investigates the questions of basic concepts and features of legal regulation of air transportation of passengers and baggage in Ukraine, namely: the legal status of the participants of the legal relationship of air transportation, contracts and commitments in sphere of air transportation, and civil liability of the subjects of air transportation.